Investment Portfolio Optimization Using Mean-Variance Model With Data Envelopment Analysis (DEA) Approach on IDX30 Stocks - Putrie, Veronica Clasrissa (International Journal of Quantitative Research and Modeling, 2025)
Globalization and technological advancements are driving the importance of careful financial management, including in investments. Stocks have become a popular investment option as they offer potential profits from dividends and capital gains. However, the large selection of stocks in the Indonesian capital market, especially in the IDX30 index, makes investors face challenges in selecting efficient stocks and compiling optimal portfolios. Therefore, this research combines Data Envelopment Analysis (DEA) and Mean-Variance Model to screen efficient stocks and form an optimal investment portfolio. In this study, DEA is used to assess the efficiency of stocks based on company performance, while the Mean-Variance Model is used to determine the optimal weight in the portfolio by balancing risk and return. Of the 13 stocks analyzed, 9 efficient stocks were identified, namely ADRO, ASII, BBCA, BBNI, BBRI, INDF, KLBF, TLKM, and UNTR. The optimal portfolio is obtained with a risk tolerance value of 0.015, which results in an expected return of 0.00027711 and a variance of 0.00004396.